Adiposidade abdominal e sua relação com consumo alimentar, estresse e qualidade de vida de profissionais de segurança pública - Silva Neto, Luiz Claudio Barreto (2024)
Abdominal adiposity is a public health challenge that affects public safety personnel exposed to high levels of stress. This complex interaction between psychological and social factors can trigger adverse responses in the body, with a significant impact on quality of life. The main objective of this study was to evaluate abdominal adiposity and investigate its association with food consumption, stress levels, biochemical variables as well as quality of life in public security agents. This is a cross-sectional study carried out with 216 public safety personnel in the state of Espírito Santo. To assess symptoms of stress, food consumption and quality of life, the Stress Symptom Inventory (ISSL), the Food Consumption Frequency Questionnaire (QFCA) and the WHOQOL-bref were used, respectively. Statistical analyzes included chi-square tests, Mann Whitney tests, Poisson regression and multiple regression models (95% CI). There was a prevalence of overweight among public safety personnel (67.8%). It was observed that agents with a higher body mass index (BMI) had an increased prevalence of abdominal adiposity, indicating a significant association between these variables (PR: 3,35 [IC95%: 3,4-5,52; p=0,001]). Furthermore, those with greater adherence to the consumption of ultra-processed foods also showed a higher prevalence of abdominal adiposity(PR: 1,68 [IC95%: 1,51- 2,47] p=0,007. Stress symptoms were associated with a 64% increase in the risk of greater abdominal adiposity, while greater adherence to ultra-processed foods demonstrated a 10% increase in the risk of abdominal adiposity. These results highlight a bidirectional relationship between stress and abdominal adiposity, highlighting the importance of stress and the consumption of ultra processed foods in increasing the risk of abdominal adiposity. Such factors can have metabolic and systemic impacts, resulting in a deterioration in the quality of life of these professionals, highlighting the urgency of interventions in this population